Centro turístico Playa Tambor - Tapia-Leandro, Randal (Instituto Tecnológico de Costa Rica, 2019)
This project is born by the necesity of making a better place in the beach of Tambor at Cóbano Puntarenas. In the present the main problema is that this site goes unnoticed by tourists. It is proposed to create a series of zones with specific functions that help improve the use of the ZMT. Generating in the first place infrastructure that supports tourist activities in Tambor and then infrastructure that allows the training of the locals so they can generate the knowledge to give better products and services to the tourist and themselves. The project consist of 3 stages, the fist one is the insfraestrucuture that pretends to economical reactivate the area by bringing tourist to the beach. The second is the make over to the Community Hall, so they can have a place to make activities such like educational workshops and reuniones with all the members of the differents civil associations in Tambor. Finally the third stage aims to create a serious of landmarks to atract tourist from all over Nicoya.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2019
Keywords: Centros turísticos -- Diseño arquitectónico; Turismo